Hard Disk Drive Servo Systems - Chen, Ben M.; Lee, Tong Heng; Peng, Kemao; Venkataramanan, Venkatakrishnan (Advances in Industrial Control, 2006)
The second edition of this monograph provides a systematic treatment of the design of modern hard disk drive servo systems updated with the latest research results to reflect recent improvements in spindle speed and bit density and other changes in this fast-moving field. In particular, it focuses on the applications of some newly developed results in control theory, i.e., robust and perfect tracking control and composite non-linear feedback control which are suitable for track following and seeking respectively. Emphasis is placed on hard disk drive servo systems with single- or dual-stage actuation using a voice-coil-motor actuator enhanced in the latter case by the addition of a micro-actuator providing faster responses and therefore higher bandwidth in track following. Other issues such as modeling and compensation of nonlinearities and friction in microdrives, disturbance rejection and resonance compensation are also addressed. The techniques and applications involved include: • time- and frequency domain methods for system identification; • physical effect approaches for parameter identification; • linear systems tools; • linear control techniques (PID, H2, H-infinity, and other robust control methods); • classical nonlinear control techniques (time-optimal, proximate time-optimal, and mode switching control); • composite nonlinear feedback (CNF) control; • complete single- and dual-stage hard disk drive servo systems; • time- and frequency domain properties of hard disk drive servo systems; • design of piezoelectric actuator systems; • modeling and compensation of nonlinearities and friction in microdrives. Hard Disk Drive Servo Systems will be of great value to practicing engineers in the hard disk and CD-ROM drive industries and to researchers in areas related to servo systems. The Linear Systems and CNF MATLAB® toolkits used to develop many of the results in this book can be downloaded from Professor Chen's website. Advances in Industrial Control aims to report and encourage the transfer of technology in control engineering. The rapid development of control technology has an impact on all areas of the control discipline. The series offers an opportunity for researchers to present an extended exposition of new work in all aspects of industrial control.